Effect of surface morphology and microstructure on the hot corrosion behavior of TiC/IN625 coatings prepared by extreme high-speed laser cladding. (June 2022) - Chen, Lan; Zhang, Xinzhou; Wu, Yue; Chen, Chen; Li, Yongjian; Zhou, Wangfan; Ren, Xudong
Abstract: Extreme high-speed laser cladding (EHLA) was used to develop a pore- and crack-free TiC/IN625 coating. The surface roughness of EHLA could be as low as 6.004 µm. A more uniform dendrite size and composition distribution was obtained by EHLA. The mass gain of EHLA was 57.5% lower than that of the conventional laser cladding sample after hot corrosion in a mixed salt of 75%Na2 SO4 + 25% NaCl at 900 ℃ for 60 h. High hot corrosion resistance of EHLA was mainly attributed to the lower surface roughness, smaller dendrite size, smaller grain size, and higher amount of low-angle grain boundaries. Highlights: Pores- and cracks-free TiC/IN625 coatings over AISI 1045 steel were firstly prepared by EHLA. EHLA TiC/IN625 coatings possessed much more uniform and finer microstructure. The uniformly distributed dendrite sizes and compositions contributed to the formation of a dense oxide film. Superior hot corrosion behavior of EHLA TiC/IN625 coatings was mainly attributed to the lower surface roughness, smaller dendrite size, smaller grain size, and more low-angle grain boundaries.